Functioning, disability, health and quality of life in adults with cerebral palsy more than 25 years after selective dorsal rhizotomy: a long-term follow-up study during adulthood - Veerbeek, Berendina Egbertine (Division of Neurosurgery, 2020)
Cerebral palsy (CP) is the most common cause of physical disability in childhood. Today, most children with CP survive into adulthood with life expectancies similar to typically developing (TD) adults. One of the biggest challenges during the lifespan of individuals with CP is healthy aging; to prevent or minimize the secondary effects of CP on the musculoskeletal system (e.g. bone deformities due to spasticity) as well as to improve functional status and quality of life. There is currently no treatment that is able to cure the brain damage which causes CP, but a variety of options exist to address spasticity, the most prevalent primary condition which is estimated to be present in 80% of people with CP. One of these options is the neurosurgical procedure of Selective Dorsal Rhizotomy (SDR) which entails selective sectioning of dorsal rootlets in the lumbosacral area, diminishing spasticity through reducing muscle tone. SDR gained increasing acceptance following the work of Peacock and Arens in the 1980s, and although a large number of studies have demonstrated the benefits of this procedure, they largely comprise relatively short-term follow-up assessments in children and adolescents. There is thus a need for long-term follow-up studies focussed on all facets of daily living (International Classification of Function, Disability and Health (ICF) model domains: body structure and function, activity and participation) and quality of life in adults with CP who underwent SDR in their childhood. The aim of this doctoral thesis was to address this need, and provide information that might help guide parents, caregivers and clinicians in their clinical decision-making process for a child with CP. This aim was addressed through three key investigations. First, the status of adults with CP and spastic diplegia - related to all domains of the ICF-model and health-related quality of life - was determined more than 25 years after SDR. Second, changes in gait pattern, spinal deformities and level of activities and participation in adults with CP were determined nine years after a similar assessment. Third, associations between results in the different ICFmodel domains along with personal and environmental context factors. This PhD thesis forms part of a longitudinal investigation tracking the health and wellness of adults with CP. The former studies were performed in 2008 and consequently a recent follow-up was conducted in 2017 in the same CP cohort. All participants underwent SDR according to the Peacock method (strict selection criteria were adhered) at Red Cross War Memorial Children’s Hospital in Cape Town, South Africa, between 1981 and 1991. This PhD thesis is based on four studies, with the first being a cross-sectional study conducted in 2017 (Chapter 2) and the other three are nine-year follow-up studies (comparing findings in 2017 with studies conducted in 2008 (Chapter 3 - 5). Each study included a matched TD group, except for the spine study (Chapter 4). Participants were observed and assessed for functioning, health, disability and quality of life based on a physical examination, gait analysis, functional mobility tests, spine radiographs and several questionnaires. With respect to the ICF-model Body structure and function domain, adults with CP showed sustained reduction in muscle tone and minimal signs of spasticity in their gait pattern, with no increased prevalence of scoliosis, hyperkyphosis or hyperlordosis, and did not experience limitation of daily activities due to pain. Some challenges were found regarding ROM, muscle strength, selectivity and back pain but they were comparable with what would be expected in adults with CP who did not undergo SDR. Concerning, the Activity domain, the majority of the cohort was independent in functional mobility and the accomplishment of daily activities with no increased risk for falls. They were as satisfied with accomplishing daily activities as the TD adults, though as might be expected, they were found to be less content with their level of mobility. Regarding Participation domain, the adults with CP greater than 25 years post-SDR were independent and satisfied with their attainment of social roles. Most were married or had a relationship, lived independently (with or without partner), finished higher education and were engaged in paid employment. The perceived health-related quality of life was similar to that of TD adults in most of the health concepts (physical role functioning, bodily pain, general health, vitality, social functioning, emotional role functioning and mental health), except for physical functioning. No increased prevalence of anxiety and depression was found, which was in line with the reported mental health findings of the health-related quality of life questionnaire. This suggests that while adults with CP have on-going physical challenges following SDR, this might not directly impact their mental health and levels of anxiety and depression. The majority of the cohort viewed the SDR they had undergone as worthwhile due to mobility and functional walking gains. Importantly, no changes were found over the nine-year interval in overall gait, functional mobility, spinal deformities, pain and level of accomplishment and satisfaction in daily activities and social participation. This indicates stability of function which is remarkable since functional decline might be expected in adults with CP while aging. However, correlations were found between functional mobility and daily activities and social participation as well as between functional mobility and strength. This highlights the possible importance of resistance training and maintaining walking ability to enable daily activities and social participation and prevent functional deterioration in the future.